Convergence of Using English Teaching Media for Sunday School Children - Otta, Gracia M. N.; Lasmawan, I Wayan; Parmiti, Desak Putu (GoAcademica Research & Publishing, 2025)
Sunday school is an important part of the church, serving as one of its educational units, and plays a crucial role in shaping children's personal character, faith, and responsibility. Throughout the teaching provided in Sunday School, it is hoped that participants will be motivated to grow in faith and develop their character, becoming stronger in their relationship with God and more competent to face life physically and mentally. The purpose of this study is to discuss the use of media in learning activities in Sunday School and the correlation of the use of such media. The results of the study show that the use of media in learning English in Sunday school can increase interest and motivation, improve English language skills, and increase their self-efficacy.